Understanding the translocation mechanism of PLGA nanoparticles across round window membrane into the inner ear: a guideline for inner ear drug delivery based on nanomedicine - Zhang L (Dove Medical Press, 2018)
Liping Zhang,1–3 Yuan Xu,1 Wenjuan Cao,1 Shibao Xie,1–3 Lu Wen,1 Gang Chen1–3 1School of Pharmacy, 2Guangdong Provincial Key Laboratory of Advanced Drug Delivery, 3Guangdong Provincial Engineering Center of Topical Precise Drug Delivery System, Guangdong Pharmaceutical University, Guangzhou, China Background: The round window membrane (RWM) functions as the primary biological barrier for therapeutic agents in the inner ear via local application. Previous studies on inner ear nano-drug delivery systems mostly focused on their pharmacokinetics and distribution in the inner ear, but seldom on the interaction with the RWM. Clarifying the transport mechanism of nanoparticulate carriers across RWM will shed more light on the optimum design of nano-drug delivery systems intended for meeting demands for their clinical application. Methods: The poly (lactic-co-glycolic acid) nanoparticles (PLGA NPs) encapsulating coumarin-6 were prepared by emulsifying solvent evaporation method. We utilized confocal laser scanning microscope (CLSM) in combination with transmission electron microscope to investigate the transport pathway of PLGA NPs in the RWM. Simultaneously, the concentration and time dependence of NPs across the RWM were also determined. The endocytic mechanism of NPs through this membrane interface was classically analyzed by means of various endocytic inhibitors. The intracellular location of NPs into lysosomes was evaluated using CLSM scanning microscope colocalization analysis. The Golgi-related inhibitors were employed to probe into the function of Golgi and endoplasmic reticulum (ER) in the discharge of NPs out of cells.Results: PLGA NPs were herein transported through the RWM of a sandwich-like structure into the perilymph via the transcellular pathway. NPs were internalized predominantly via macropinocytosis and caveolin-mediated endocytic pathways. After being internalized, the endocytosed cargos were entrapped within the lysosomal compartments and/or the endoplasmic reticulum/Golgi apparatus which mediated the exocytotic release of NPs.Conclusion: For the first time, we showed the translocation itinerary of NPs in RWM, providing a guideline for the rational fabrication of inner ear nanoparticulate carriers with better therapeutic effects. Keywords: poly (lactic-co-glycolic acid) nanoparticles, round window membrane, endocytotic mechanism, exocytotic mechanism, inner ear